Ω-3 Polyunsaturated Fatty Acids Facilitate the Repair of Peripheral Nerve Defects with Chemically Extracted Acellular Allograft in Rats. (27th January 2021) - Zuo, Jun; Wu, Yuan; Xiang, Renkun; Dai, Zhiping; Zhu, Yi
Abstract : Acellular allograft (ACA) improves the repair and reconstruction of long peripheral nerve defects. ω -3 Polyunsaturated fatty acids (PUFAs) carry a neuroprotective potential, and their effects on ACA bridging were elucidated. Thirty rats with long gap sciatic nerve defects (15 mm long) were randomly divided into three groups (n = 10 ): ACA, ACA + PUFAs, and autograft (AU). Limb condition, wet weight of tibialis anterior muscle (TAM), nerve electrophysiology, S-100, horseradish peroxidase (HRP), and percentage of splenic CD4+ and CD8 + T-lymphocytes were evaluated for 12 weeks after the operation. Rats in the AU and ACA + PUFA groups showed superior condition in affected limbs compared to the ACA group. At 12 wk after surgery, the wet weight of TAM in the ACA + PUFA group was higher than that in the ACA group (0.4519 ± 0.1185 vs. 0.3049 ± 0.1272 ; P < 0.01 ) but lower than that in the AU group (0.4519 ± 0.1185, 0.5628 ± 0.0092 ; P < 0.05 ). In all the three groups, sole irritation elicited withdrawal reflex, and S-100 staining was detected in plantar skin. Moreover, horseradish peroxidase staining was overt in both the ventral horn and dorsal root ganglion of the spinal cord. Nerve conduction velocity (m/s), amplitude of action potential (mV), or somatosensory evoked potentials in ACA + PUFAs (28.81 ± 1.04, 2.20 ± 0.27, 6.98 ± 0.29 ) were significantly different from that in the AU (35.71 ± 1.28, 1.81 ± 0.19, 8.15 ± 0.52 ; P < 0.05 ) and ACA (20.03 ± 1.94, 2.95 ± 0.36, 5.22 ± 0.53 ; P < 0.01 ) groups. The percentages of splenic CD4+ and CD8+ cells were similar among the three groups. Omega-3 PUFAs improve the bridging effect of ACA on long gap peripheral nerve defects by promoting neuroprotection without arousing an immune response.